The relation of food to the advancement of civilization - Burtner, Nellie (My University, 1900)
Introduction: This is an age of industrial and political reform just as truly as the period of The Reformation and the French Revolution, though unaccompanied with the inhumanity and carnage which attended these upheavals. The Caucasian race is far in advance of the barbarous methods of progress. In the future the reforms will be brought about gradually, and the word reform will lose its terror and be changed to a word meaning simply advancement only. Science is quietly revolutionizing the world by exploding many of the old theories which have stood for decades. The search for truth is growing more and more zealous and extensive. It is revealing more and more of the fundamental principles of life, and the extensive studies in Physiology and Psychology are permitting a keen insight into the laws governing the mental and moral habits of man. Not satisfied still, he has penetrated the bowels of the earth, and explored the mysteries of the heavens with the gigantic telescope. The chief end of all this research is to benefit and uplift man. Experience long has taught us that all races are not alike susceptible to learning, nor is it confined to any one. Caucasian race includes the most civilized people in the world, and it occupies the most desirable portions of the globe. This people is characterized by its industry morality and brain energy. Their history has been one of progress and triumph, which is manifested in many ways, viz. intellect, mode of living, surroundings, food, social and political relations, and morality. To treat these fully, would require many volumes or to treat any one accurately would fill a large book. In the following one will confine ourselves to the discussion of the food of a nation in regard to its degree of civilization.
Citation: Burtner, Nellie. The relation of food to the advancement of civilization. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Food; Nutrition; Anthropology; Theses